2014
DOI: 10.1117/12.2064536
|View full text |Cite
|
Sign up to set email alerts
|

History of the Shack Hartmann wavefront sensor and its impact in ophthalmic optics

Abstract: The Shack Hartmann wavefront sensor is a technology that was developed at the Optical Sciences Center at the University of Arizona in the late 1960s. It is a robust technique for measuring wavefront error that was originally developed for large telescopes to measure errors induced by atmospheric turbulence. The Shack Hartmann sensor has evolved to become a relatively common non-interferometric metrology tool in a variety of fields. Its broadest impact has been in the area of ophthalmic optics where it is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…A variant of this test is known as Hartman-Shack [81]. Developed for defense purposes during the cold war by Roland Shack.…”
Section: B Pattern Reflectionmentioning
confidence: 99%
“…A variant of this test is known as Hartman-Shack [81]. Developed for defense purposes during the cold war by Roland Shack.…”
Section: B Pattern Reflectionmentioning
confidence: 99%
“…This technique was used to test the optics of the "Great Refractor" telescope. 1 Later, in 1971, Platt and Shack proposed using a lenticular screen instead of using the screen constructed by Hartmann, but using the same principle, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of studies have focused on improving the center of gravity (CoG) method [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], but, if the aberration to be measured is too large and the fluctuation of the wavefront is too steep, it will cause some sub-aperture spots to deviate from the corresponding sub-aperture. This condition is commonly measured in patients with severe refractive errors and patients who have undergone corneal or lens surgery [ 17 , 18 ]. Carmen Canovas and Erez N. Ribak compared and analyzed SHWFS methods (convolution, interpolation, Fourier methods, and centroid methods) for ophthalmology, and found that the Fourier method has the best effect for pupils with a small slope of the boundary or with a large distance from the boundary [ 19 ].…”
Section: Introductionmentioning
confidence: 99%